Kinematic comparison of double poling techniques between national and college level cross-country skiers using wearable inertial measurement unit sensors - Choi, Y. C.; Khuyagbaatar, B.; Cheon, M.; Batbayar, T.; Lee, S.; Kim, Y. H. (International Journal of Precision Engineering and Manufacturing, 2021)
This study aimed to analyze and compare the hip, knee, and elbow joint movements during the double poling (DP) technique in cross-country skiing using a wearable inertial measurement unit (IMU) sensor on a real snow skiing track. Six national players (NP) and five college players (CP) participated in this study. The joints angles were calculated using the data from IMU sensors on a 145 m skiing course with 10° slope using the DP technique. In addition, the parameters of the DP phase were estimated. Then, all parameters were compared between the NP and CP groups. The hip and knee joint angles in the NP groups were significantly larger than the CP groups. However, there was no intergroup difference in elbow joint range of motion (ROM). Moreover, the cycle length and cycle velocity was higher in the NP group than the CP group. The results showed that the NP group had higher speed and longer cycle length with greater flexion angles in the hip and knee joints. The wearable IMU sensor was used to analyze the motions during DP skiing on the snow skiing slope, which can provide more realistic detailed analysis of the skiing movements. This study provides the comparison analysis of the main parameters between the two different skilled skiers groups, which may help coaches and players improve skiing performance.